Boxed and labelled : new approaches to packaging design. - Klanten, Robert, 1964- (Berlin : Gestalten, 2009)
Trends in the visual and graphic language of state-of-the-art packaging design. Packaging is the face and visual identity of a product and can also be the cru- cial determining factor in the buying decision when a product is lined up on a crowded store shelf. As consumer tastes become more complex and culturally diverse, packaging increasingly requires a visual and graphic language that targets aesthetics as well as the needs of the discerning twenty-first-century shopper. Boxed and Labelled is a comprehensive overview of the most intelligent, innovative, playful and attractive examples of current packaging design. The broad spectrum of packaging is illustrated through an extensive selection of products characterised by cutting-edge graphic design, sassy illustrations, striking typography, careful use of colour as well as unique materials. The exam- ples in the book run the gamut from jam jars, chocolate wrappers, wine labels, champagne bottles and perfume flacons to sneaker boxes and shopping bags. The book also highlights extraordinary projects that have a unique approach to functionality, surplus value and sustainability, in addition to stimulating concepts that amount to pure seduction. This book demonstrates the diverse solutions designers have found to deal with many different themes such as creating approachability through a whimsical and lighthearted appearance and material surfaces or promoting value and trustwor- thiness or conveying a handmade feeling to an artisanal product with a sophis- ticated, refined and purposeful look. All of the featured examples deliver their own unique brand valuesand experiences and set them apart in the competitive marketplace. Boxed and Labelled offers exciting solutions and presents state-of- the-art packaging design today.